Retinal optical coherence tomography changes as biomarkers for Parkinsonism duration and severity in the Kashmiri population - Irtiqa Mohammad; Sabia Rashid; Bashir A. Sanie; Shubana Ashraf; Adnan F. Raina (Annals of Movement Disorders)
BACKGROUND: Parkinson’s disease (PD) is a progressive neurodegenerative disorder with motor and non-motor symptoms, including visual disturbances. The retina, being an extension of the central nervous system, may serve as a potential biomarker for PD and related disorders. AIMS AND OBJECTIVES: To evaluate retinal morphological changes using optical coherence tomography (OCT) in patients with PD and atypical parkinsonian syndromes and to correlate these changes with disease duration and severity. METHODS: This cross-sectional study included 50 parkinsonian patients (37 idiopathic PD, 5 multiple system atrophy [MSA], 4 corticobasal degeneration [CBD], 4 progressive supranuclear palsy [PSP]) and 50 age-matched healthy controls. Retinal parameters, including central macular thickness, macular volume, ganglion cell layer–inner plexiform layer (GCL–IPL) complex thickness, inner plexiform layer to outer nuclear layer (IPL–ONL) thickness, and retinal nerve fiber layer (RNFL) thickness, were assessed using OCT. RESULTS: The mean central macular thickness was significantly lower in cases (229.10 ± 36.61 μm) compared to controls (271.67 ± 19.03 μm) (P < 0.001). Macular volume was also lower in cases (8.91 ± 0.90 mm³) versus controls (9.21 ± 0.52 mm³) (P = 0.01). The GCL–IPL complex thickness (57.98 ± 20.22 μm vs. 86.93 ± 6.51 μm), IPL–ONL thickness (165.45 ± 13.74 μm vs. 174.06 ± 7.78 μm), and RNFL thickness (75.10 ± 23.12 μm vs. 94.51 ± 7.57 μm) were significantly lower in cases compared to controls (P < 0.001). Progressive supranuclear palsy patients had the lowest central macular thickness, macular volume, and GCL–IPL complex thickness, while corticobasal degeneration patients had the lowest IPL–ONL thickness, and multiple system atrophy patients had the most reduced RNFL thickness. CONCLUSION: This study demonstrates significant retinal morphological changes in parkinsonian patients, suggesting the potential use of the retina as a biomarker for PD and related disorders. Patients with PSP exhibited the most pronounced retinal changes, indicating diagnostic value. Further large-scale studies are warranted to establish the clinical utility of OCT in the management of these neurodegenerative conditions.